2021
DOI: 10.3390/biomedicines9091186
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of the Adeno-Associated Virus Vector, AAV6.2FF, Expressing a Monoclonal Antibody in Murine and Ovine Animal Models

Abstract: Adeno-associated virus (AAV) vector mediated expression of therapeutic monoclonal antibodies is an alternative strategy to traditional vaccination to generate immunity in immunosuppressed or immunosenescent individuals. In this study, we vectorized a human monoclonal antibody (31C2) directed against the spike protein of SARS-CoV-2 and determined the safety profile of this AAV vector in mice and sheep as a large animal model. In both studies, plasma biochemical parameters and hematology were comparable to untre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Indeed, we have shown that AAV-mediated expression of human IgG1 mAbs is feasible in mice, 26 Syrian hamsters, 27 and sheep. 28 More recently, data from a phase 1, dose-escalation clinical trial (NCT03374202) evaluating AAV8-mediated expression of the broadly neutralizing anti-HIV mAb VRC07 from an expression cassette that we based our EBOV mAb expression platform on in this body of work is encouraging in that all eight individuals produced measurable amounts of serum VRC07, with maximal concentrations >1 mg/mL in three participants. 46 In four individuals, VRC07 serum concentrations remained stable near maximal concentration for up to 3 years of follow-up, and unlike the first human clinical trial to evaluate AAV-mediated expression of an HIV bNAb, ADA responses were observed in only three of eight participants, and only in two cases did this lead to decreased serum VRC07, demonstrating that AAV-mAb expression is potentially a viable alternative platform for protection against infectious diseases.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, we have shown that AAV-mediated expression of human IgG1 mAbs is feasible in mice, 26 Syrian hamsters, 27 and sheep. 28 More recently, data from a phase 1, dose-escalation clinical trial (NCT03374202) evaluating AAV8-mediated expression of the broadly neutralizing anti-HIV mAb VRC07 from an expression cassette that we based our EBOV mAb expression platform on in this body of work is encouraging in that all eight individuals produced measurable amounts of serum VRC07, with maximal concentrations >1 mg/mL in three participants. 46 In four individuals, VRC07 serum concentrations remained stable near maximal concentration for up to 3 years of follow-up, and unlike the first human clinical trial to evaluate AAV-mediated expression of an HIV bNAb, ADA responses were observed in only three of eight participants, and only in two cases did this lead to decreased serum VRC07, demonstrating that AAV-mAb expression is potentially a viable alternative platform for protection against infectious diseases.…”
Section: Discussionmentioning
confidence: 92%
“…ZMapp was dosed at 50 mg/kg over multi-day treatment courses in humans to maintain a therapeutic threshold 9 ; however, much lower but more consistent serum mAb concentrations mediated by AAV6.2FF should be able to maintain therapeutic efficacy without the peak and trough pharmacokinetics associated with repeat recombinant mAb administration. 45 There is strong evidence of the prophylactic efficacy of AAV6.2FF-mAb therapies, [26][27][28] allowing for post-exposure use to extend the potential applications of this therapy. Potential exposures to EBOV in a lab accident or health-care setting are realistic possibilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At last but not least, a recent study demonstrated that AAV6-based mutant could steadily express transgene at a high level in sheep by intramuscular injection 56 . Another research showed that AAV6 can efficiently infect the muscle tissue adjacent to the injection site through subcutaneous injection and induce detectable T cell responses against transgene 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous AAV serotypes with variable tropism exist [ 33 ], the novel triple-mutant AAV6.2FF capsid, which possesses an amino acid substitution (F129L) that facilitates heparin binding (AAV6.2) at the cell surface [ 50 ], and two mutations (Y445F, Y731F) that abrogate ubiquitin-mediated degradation [ 51 ], represents and ideal candidate for in vivo expression of antiangiogenic compounds due to its ability to mediate rapid and sustained transgene expression following intramuscular administration [ 52 , 53 ]. In a head to head comparison, AAV6.2FF outperformed other commonly used AAV capsids including AAV6, AAV8, AAV9, and DJ, by expressing significantly more luciferase in the first 14 days post-administration [ 54 ].…”
Section: Introductionmentioning
confidence: 99%